The Effect of Leadership Behavior and Organizational Climate on the Performance of Teaching Staff at the State Police School Polda Maluku - Daniel Prio Dwi Atmoko; R. Kempa; A. Sahalessy (Peneliti.net, 2022)
This research was conducted with the aim of (1) describing leadership behavior, (2) describing organizational climate, (3) describing the performance of teaching staff at the Maluku police state police school, (4) knowing the significant influence between Leadership Behavior on Teaching Staff Performance, (5) Knowing the significant influence between Organizational Climate on Teaching Staff Performance, (6) Knowing the significant influence between leadership behavior and Organizational Climate on Teaching Staff Performance at the Maluku Police State Police School. Based on the results of the description of the principal's leadership behavior, respondents gave high criteria with a presentation of 64.37% with an average value of 136.23, the respondent's organizational climate gave high criteria for a presentation of 42.53% with an average value of 115, 36. and for the performance of the principal teaching staff, the respondents gave very high criteria with a presentation of 57.47% with an average score of 163.06. While the results of the leadership variable hypothesis test (X1asignificant influence between leadership behavior on the performance of the Maluku Regional Police SPN teaching staff with a determination coefficient of 0.714, the results of the organizational climate variable hypothesis test (X2) showed a significant influence between organizational climate on performance teaching staff of SPN Polda Maluku with a coefficient of determination of 0.611 which means that the influence of organizational climate on the performance of teaching staff contributes 61.1%. The results of the hypothesis test of the leadership behavior variable (X1) and organizational climate (X2 indicate a jointly significant influence on the performance of the Maluku Regional Police SPN teaching staff with a coefficient of determination of 0.730%, which means that the influence of organizational climate on the performance of teaching staff contributes 73, 0%,